Phenolic acids and ruminal parameters of different varieties of sugarcane in natura or ensiled - Spínola, Jaime Emerson Laranjeira; Reis, Sidnei Tavares Dos; Sales, Eleuza Clarete Junqueira De; Monção, Flávio Pinto [UNESP]; Rigueira, João Paulo Sampaio; Delvaux, Nelson De Abreu (Editora da Universidade Estadual de Maringá - EDUEM, 2017)
This study aimed to determine and measure the phenolic acids in four varieties of sugarcane (RB 855536, RB 765418, SP 80-1842 and SP 80-1816) as fresh and ensiled, and assess the influence of these acids on in situ degradability of dry matter and neutral detergent fiber. The experimental design was completely randomized in a factorial design. For the fraction of dry matter (DM), varieties RB 855536 and SP 80-1842 had average 17.80% higher compared to others. The SP80-1842 and RB 855536 varieties did not differ (p > 0.05), with an average of DM effective degradability of 33.70%. For silage, the highest levels of p-coumaric acid were found in the variety RB 855536, which was 24.64% higher than the varieties RB 765418 and SP 80-1842 (average 12.75%) and 52.60% of the variety SP 80-1816 (average 8.02%), since for the in natura form, varieties did not differ between each other (p > 0.05), and had an average of 8.86%. Silage variety SP 80-1816 has ferulic acid content 40.82% higher than the other varieties, with an average of 4.63%. The examination of the concentrations of phenolic acids p-coumaric and ferulic are not sufficient to justify the effect of microbial action on the varieties studied in different forms of processing.

Objetivou-se determinar e mensurar os ácidos fenólicos em quatro variedades de cana-de-açúcar (RB 855536, RB 765418, SP 80-1842 e SP 80-1816) na forma in natura e ensilada, bem como avaliar a influência destes ácidos sobre a degradabilidade in situ da matéria seca e fibra em detergente neutro. O delineamento experimental foi inteiramente casualizado em esquema fatorial. Para a fração da matéria seca (MS), as variedades RB 855536 e SP 80-1842 tiveram médias 17,80% superior em relação às demais. As variedades SP 80-1842 e RB 855536, não diferiram entre si (p > 0,05) com média de degradabilidade efetiva da MS de 33,70%. Para a silagem, os maiores teores de ácido p-cumárico foram constatados na variedade RB 855536 que foi 24,64% superior às variedades RB 765418 e SP 80-1842 (média de 12,75%) e 52,60% à variedade SP 80-1816 (média de 8,02%), sendo que para a forma in natura, as variedades não diferiram entre si (p > 0,05), média de 8,86%. A silagem da variedade SP 80-1816 apresentou teor de ácido ferúlico 40,82% superior às demais variedades, média 4,63%. A verificação das concentrações dos ácidos fenólicos p-cumárico e ferúlico não são suficientes para justificar o efeito da ação microbiana sobre as variedades estudadas nas diferentes formas de processamento.
Ácidos fenólicos e parâmetros ruminais de diferentes variedades de cana-de-açúcar in natura ou ensilada
Keywords: digestibility; fermentation; lignin; silage; nutritional value; digestibilidade; fermentação; lignina; silagem; valor nutricional